2018
DOI: 10.1002/zaac.201700358
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric Units [Ag3X8]5– with Face‐sharing Polyhedra in the Series Tl2AgX3 (X = Cl, Br, I): Synthesis, Crystal Structure, and Vibrational Spectra

Abstract: The ternary compounds Tl2AgX3 (X = Cl, Br, I) were obtained as colorless single crystals by reaction of the binary halides AgX and TlX (X = Cl, Br, I) together with concentrated HX solutions under hydrothermal conditions. Silica glass ampoules were filled to 50 % with these solutions and heated for several days up to 250 °C. The reaction was carried out in steel autoclaves to prevent bursting. All the compounds are isostructural and crystallize trigonally with the already known Tl2AgI3 type (R3, Z = 9), but Tl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…According to Pauling’s rule, [PbI 6 ] 4– octahedrals can be connected by common vertices, common edges, or common faces in principle. For the latter two connection modes, the repulsion between cations will increase and the stability of the crystal structure will be reduced. We measured the distance between the Pb 2+ in adjacent [PbI 6 ] 4– octahedrals in these five structures (Figure S6), and found that the C 2 and C 6 crystals with edge-sharing and face-sharing connections are shorter than those of the other three crystals with corner-sharing structures. That will result in stronger repulsion and instability of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…According to Pauling’s rule, [PbI 6 ] 4– octahedrals can be connected by common vertices, common edges, or common faces in principle. For the latter two connection modes, the repulsion between cations will increase and the stability of the crystal structure will be reduced. We measured the distance between the Pb 2+ in adjacent [PbI 6 ] 4– octahedrals in these five structures (Figure S6), and found that the C 2 and C 6 crystals with edge-sharing and face-sharing connections are shorter than those of the other three crystals with corner-sharing structures. That will result in stronger repulsion and instability of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocrystals obtained from reactions immediately quenched at 110 °C were also uniform, as shown in the TEM images in Supporting Information, Figures S2E–F and S4A–B. The XRD and electron diffraction patterns in Figures D and 4E show that the crystal structure is trigonal dolomite‐type Tl 2 AgBr 3 . The lattice fringes in the high resolution TEM image in Figure C are separated by 2.8 Å with an angle of 120° between lattice fringes, corresponding to the (300) planes.…”
Section: Resultsmentioning
confidence: 77%